Aggressive Burkitt-Like Lymphoma of Colon in a Patient With Prior Celiac Disease - Ahluwalia, M. (Yale Journal of Biology and Medicine, 2007)
Background: Celiac disease (CD) and immunosuppression are the two risk factors for gastrointestinal, as well as non-gastrointestinal, non-Hodgkin’s lymphomas (NHL). Recent large retrospective studies confirm that celiac disease significantly increases risk of developing small bowel lymphomas by 30 to 40 percent and other gut malignancies by 83-fold. Case Report: A 75-year-old man with a history of CD of two-year duration presented with pallor, fatigue, and 20-pound weight loss of three weeks duration. There was a vague non-tender mass in the right hypochondrium, and his stools tested positive for occult blood. The lab values were within normal range, except for hemoglobin of 11mg/dL, MCV 75, mildly elevated SGOT of 61 IU/L, and LDH of about 5000 IU/L. Work-up including computerized tomography (CT) scan, positron emission tomography (PET) scan, and colonoscopy were performed. Results: A CT scan of the abdomen showed extensive carcinomatosis, scattered lymphadenopathy, and small pleural effusions. PET scan results coincided with CT findings. Colonoscopy revealed a friable nodular mass in the hepatic flexure, histopathology of which confirmed a high-grade B-cell lymphoma. Flow cytometry following immunostaining was positive for CD10, CD19, CD20, CD45, CD79a, and Ki-67. FISH assay demonstrated t (14:18) translocation and bcl-2 rearrangement. The bone marrow biopsy showed evidence of disease. The patient was treated with rituximab, plus cyclophosphamide, Adriamycin, vincristine, and prednisone (CHOP-R), with intrathecal methotrexate prophylaxis. Currently, the patient remains in remission. Conclusion: This is the first case of aggressive Burkitt-like lymphoma (BLL) occurring in a patient with celiac disease in his eighth decade of life. It is possible that chronic inflammation, profound immunosuppression, and nutritional deficit could lead to development of high-grade B-cell lymphoproliferative disorders. Further molecular studies are warranted to the investigate the link between certain polymorphisms of human leukocyte antigens (HLA) in B-cell populations in the gut, and this might be useful to identify high-risk individuals in the population of patients with CD.